Comparison between the Young and Elderly Diagnosed Patients of Carcinoma of the Breast : Breast Carcinoma in Young and Elderly Patients - Khan, Ramsha; Javed, Umar; Ur Rehman, Atiq (Pakistan Journal of Health Sciences, 2024)
Breast cancer presents a significant health challenge in Pakistan, marked by high incidence rates and specific cultural and societal barriers to early detection and treatment. Objective: To compare diagnosed cases of CA breast in younger and older patients in terms of mode of presentation, TNM stage at presentation, histological variety and hormonal status. Methods: In our prospective comparative study conducted at the Department of Surgery, Bahawal Victoria Hospital, Bahawalpur, we included a total of 220 breast cancer patients aged 20 years and above. Patients were stratified into two distinct age groups for comparison: younger patients (aged less than or equal to 35 years) and older patients (aged more than 35 years). Modes of presentation, histological types, and hormonal receptor statuses were compared between the both groups. Results: In a study of 220 breast cancer patients with a mean age of 42.97 years, younger patients (≤35 years) constituted 24%, while older patients (>35 years) made up 76%. The most common presentation was lump formation (78.18%), mainly in older patients. Ulceration was evenly distributed across age groups. Histologically, invasive ductal carcinoma Grade III was more frequent in older patients, whereas Ductal Carcinoma In Situ (DCIS) was exclusive to younger patients, underscoring distinct age-related disease patterns. Conclusions: Our study revealed significant age-related differences in breast cancer presentation among Pakistani patients. Older patients (>35 years) predominantly presented with lump formation, suggesting diagnostic delays, while all younger patients (≤35 years) had DCIS, indicating possible early detection or unique tumor biology. Additionally, older patients exhibited higher ER and PR positivity.